g(x) = -(x + 1)^2 - 3
Let's simplify this equation
g(x) = -(x^2 + 2x + 1) - 3
Distribute the negative sign
g(x) = -x^2 - 2x + 1 - 3
Combine like terms
g(x) = -x^2 - 2x - 2
The value of a = -2 and this value is LESS THAN 0
Umm Do you have A Picture For It Cause If You Don't Then I Can't Answer It
Answer:
b
Step-by-step explanation:
Answer:
{2, -3, -3/2}
Step-by-step explanation:
hi! we can set each of the binomials equal to 0 to find the zeros of this polynomial.
x-2=0
x=2
x+3=0
x=-3
2x+3=0
2x=-3
x=-3/2
Us photo math , it show u even the steps of how was it solve